Fine Structure Analysis of White Spot Syndrome Virus of Shrimp - Amano, Yasuji; Diaz C., Linda; C., Jose Melena (Brazilian Journal of Veterinary Pathology, 2011)
White Spot Syndrome Virus (WSSV) was isolated from diseased shrimps presenting with clinical signs of WSSV infection. The seed virus was identified as WSSV by PCR, and used to inoculate to specific pathogen free (SPF) P. vannamei bloodstocks. WSSV was purified as described by Huang from infected gills from inoculated animals that were homogenized in a blender and partially purified by differential centrifugation. The final purification was carried out using density gradient in 10-40% NaBr and purified virus used for morphological analysis using transmission electron microscopy. A negative staining method using 2% PTA was used for purified virus, and electron staining with lead citrate and uranylacetate was used for ultra thin sections of infected tissues. This analysis determined that i) the spikes of intact virions could be clearly identified on the virion surface and on a partially broken envelopes, ii) the nucleocapsid structures were similar to those previously reported, even though the so called "ring" structure described previously was different and, iii) negative staining of purified WSSV fractions identified nucleosome like structures.